Avaliação de transtornos de personalidade e padrões comportamentais da alienadora parental - Lass, Ruth Berenice (2013)
Although parental alienation has been discussed in different contexts, little is known about the psychological characteristics of the alienating parent. The aim of this study was to assess behavior patterns and the possible correlation of parental alienation and personality disorders in the alienating mother. A research was conducted involving 05 families in process of child custody litigation, with evidences of parental alienation . Participants were referred by family Courts for custody evaluation. Besides the triad child, mother and father, members of the extensive family such as grandparents, uncles, current spouses and step parents were interviewed. Unstructured interviews were held in order to obtain family history data, semi structured interviews were held to identify DSM-IV-TR criteria for 06 personality disorders and to assess behaviors patterns and strategies of the alienating parent. With the children semi structured interviews were used to verify the level of the alienation in the children and they responded to a parental styles inventory in order to correlate poor parenting practices and parental alienation. The results seem to confirm evidences of paranoid and narcissistic personality disorders in the alienating parent in severe cases of parental alienation.